Learners’ Characters in Post Truth Era: A Critical Study of the book of Izhatun Nasyi’in by Syekh Mustafa Al-Ghalayaini - Nasikhin - Nasikhin; Raharjo - Raharjo; Nasikhin - Nasikhin (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2022)
The United Nations International Children's Emergency Fund (UNICEF) stated that in 2016, 50% of 33 million Indonesian youth have committed acts of violence due to misinformation. This incident occurred as a result of the proliferation of post truth   phenomena which are increasingly dangerous. This study aims to describe the character of learners in the post truth era in the perspective of Shaykh Mustafa al-Ghalayaini in his book, Izhatun Nasyi'in. Using library research method, this research explored the concept of learners’ characters that should be possessed in responding to the post truth phenomenon. The results showed that the learning characters offered by Shaykh Musthafa al-Ghalayaini were intensive coaching, mentoring, and giving advice. Then the process of character building was based on the character values needed by students in responding to post truth phenomena such as being patient, not using religion for personal commercial purpose, having hopes and dreams, courage, prioritizing the benefit of the people, renewal, being religious, liking to read ,nationalist, will, simple, and trustworthy. These attitudes are the description of learners’ characters to fight the negative impact of post truth that occurs among teenagers.